Cigarette smoking and bladder cancer risk: an evaluation based on a systematic review of epidemiologic evidence in the Japanese population. (17th January 2016) - Masaoka, Hiroyuki; Matsuo, Keitaro; Ito, Hidemi; Wakai, Kenji; Nagata, Chisato; Nakayama, Tomio; Sadakane, Atsuko; Tanaka, Keitaro; Tamakoshi, Akiko; Sugawara, Yumi; Mizoue, Tetsuya; Sawada, Norie; et al.
Abstract: Objective: Although several epidemiological studies have demonstrated that cigarette smoking is an important risk factor for bladder cancer, no systematic review in the Japanese population has yet been performed. Accurate evaluation of bladder cancer risk in relation to smoking for Japanese populations can provide necessary information for Japanese policy-makers and doctors to enlighten the importance of smoking cessation. We reviewed epidemiologic data to estimate the strength of the association between cigarette smoking and bladder cancer in the Japanese population. Methods: We identified previous cohort and case-control studies, extracting data from databases in the MEDLINE (PubMed) and Ichushi . The magnitude of association and strength of evidence were evaluated in each study, and a meta-analysis was conducted to obtain summary estimates for the overall magnitude of association. Results: Three cohort and eight case–control studies were identified. Except for one case–control study, all studies showed a strong positive association between cigarette smoking and bladder cancer. The summary relative risk for ever smokers relative to never smokers was 2.14 (95% confidence interval 1.87–2.44) in a fixed-effect model. Conclusions: We conclude that cigarette smoking is a convincing risk factor for bladder cancer among Japanese.